Development and demonstration of PEM fuel-cell-battery hybrid system for propulsion of tourist boat. (9th February 2016) - Choi, Choeng Hoon; Yu, Sungju; Han, In-Su; Kho, Back-Kyun; Kang, Dong-Gug; Lee, Hyun Young; Seo, Myung-Soo; Kong, Jin-Woo; Kim, Gwangyun; Ahn, Jong-Woo; Park, Sang-Kyun; Jang, Dong-Won; et al.
Abstract: In this paper, we present the development and demonstration of a polymer electrolyte membrane (PEM) fuel-cell-battery hybrid system for the propulsion of a 20-m-long tourist boat. The PEM fuel-cell-battery hybrid system was developed by integrating PEM fuel cells with Li-ion batteries to supply electric power to the waterjet propulsion system and auxiliary equipment of the boat, which was operated in coastal waters. The PEM fuel cells and Li-ion batteries generated an electric power of 50 kW and stored an energy of 47 kWh, respectively. All of the system components, including the PEM fuel-cell modules, hydrogen storage tanks, DC–DC converters, Li-ion battery packs, and battery charger were newly developed and pre-tested for installation onboard, and the boat was built using an aluminum alloy to arrange the developed PEM fuel-cell-battery hybrid system inside of it. The first fuel-cell-powered boat in Korea was successfully demonstrated in the coastal waters of Busan, Korea. The demonstration exhibited the reliable operation of the fuel-cell-battery hybrid system and boat speeds of 6.6–7.8 knots at a power output of ∼85 kW. Graphical abstract: Highlights: A PEM fuel-cell-battery hybrid system is developed for a tourist boat. The system, together with Li-ion batteries, generates a power of 90 kW. A 20-m-long boat is built for arranging the system. The fuel-cell-powered boat is demonstrated in coastal waters. Boat speeds of 6.6–7.8 knots are achieved at a power output of ∼85 kW.